2017
DOI: 10.1055/s-0042-123040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Glutathione Peroxidase and KCNJ11 Gene Polymorphisms in Patients with New Onset Diabetes Mellitus After Renal Transplantation

Abstract: Genetic mutations such as C599T polymorphism in glutathione peroxidase [GPX1] gene and polymorphisms in potassium channel (KCNJ11) genes have recently been proposed in the etiopathogenesis of new onset diabetes mellitus after renal transplantation (NODAT). We aimed to examine the association of GPX1 and KCNJ11 polymorphisms in NODAT. This is a monocenter case-control study with a total of 118 renal transplant recipients who were divided into 2 groups; NODAT and normal glucose tolerance. Relation of GPX1 and KC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…In a cohort with 1244 type 2 Polish patients, the T allele and T/T genotype increased the risk of developing diabetic peripheral neuropathy [68]. Similar results were found in the Turkish population, in which the T allele was significantly more frequent in patients with new onset diabetes mellitus after renal transplantation [180]. When the evaluation of macrovascular diseases in type 2 diabetic Japanese patients was performed, the prevalence of peripheral vascular and cardiovascular diseases and the mean intima-media thickness of the common carotid arteries was higher in the Pro/Leu group when compared to the Pro/Pro group [181].…”
Section: Selenoproteins and Their Polymorphismssupporting
confidence: 71%
“…In a cohort with 1244 type 2 Polish patients, the T allele and T/T genotype increased the risk of developing diabetic peripheral neuropathy [68]. Similar results were found in the Turkish population, in which the T allele was significantly more frequent in patients with new onset diabetes mellitus after renal transplantation [180]. When the evaluation of macrovascular diseases in type 2 diabetic Japanese patients was performed, the prevalence of peripheral vascular and cardiovascular diseases and the mean intima-media thickness of the common carotid arteries was higher in the Pro/Leu group when compared to the Pro/Pro group [181].…”
Section: Selenoproteins and Their Polymorphismssupporting
confidence: 71%
“…ATP-sensitive potassium channel KCNJ11 plays an important role in the regulation of insulin secretion by pancreatic β cells, as well as glucose metabolism. KCNJ11 rs5219 glutamic acid to lysine amino acid substitution reduces potassium channels' sensitivity to ATP molecules, resulting in overactivity of the channel and subsequent inhibition of insulin secretion [ 12 , 24 , 25 ]. The meta-analysis of the Asian Indian population showed no significant association of KCNJ11 rs5219 polymorphism with risk of T2DM [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factor encoding gene HNF4A [ 12 ], genes encoding renin-angiotensin system (RAS) including ACE and AGT [ 35 , 44 ]; insulin-resistance genes of VDR ( Fox1 ) [ 33 ], adiponectin [ 34 , 40 ], and PAI-1 [ 46 ]; insulin-sensitive gene IRS [ 12 , 31 ]; glucose homeostasis genes CAPN10 [ 47 ], PPARα , and POR [ 32 , 36 ]; and inflammatory factor genes such as CCL5 [ 34 , 48 ], IL-6 [ 37 ], IL-1B , IL-2 , IL-4 , IL-17 , IL-7R, and IL-17R [ 18 , 29 , 39 ] have been shown to contribute to the pathogenesis of PTDM. Lower GPX1 enzyme activity, caused by GPX1 599C to T mutation, increases the exposure of pancreatic β cells to oxidative stress and development of PTDM [ 24 , 49 ]. Additionally, ATF6 , GST ( SOD and CAT ), INFγ and ( TGFβ1 , TNFα , and STAT4 ) polymorphisms, which play important roles in endoplasmic reticulum stress, oxidative stress, and inflammation respectively, were not found to be associated with PTDM [ 16 , 28 , 41 , 42 , 45 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…36,37 A recent case control study evaluating variants in kidney transplant recipients identified variants in the voltage-gated K+ channel (KCNQ1) gene, matrix metalloproteinase-2 (MMP2) gene and the glutathione peroxidans (GPX1) gene along with clinical factors have been reported to be associated with NODAT risk. [38][39][40][41] A recent Swiss study identified rs2114592 in the SP110 nuclear body protein (SP110) as conveying a 9.9 times higher risk for NODAT. 42 This variant was not significant in their analysis of a nontransplant white population with type 2 diabetes and the investigators hypothesized a geneenvironment interaction may be present where immunosuppressants may unmask the gene effect.…”
Section: Discussionmentioning
confidence: 99%